2014
DOI: 10.1016/j.jcrs.2014.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography–derived corneal thickness asymmetry indices: Clinical reference study of normal eyes

Abstract: Dr. Kanellopoulos is a consultant to Alcon Laboratories, Inc., Allergan, Inc., Avedro, Inc., Keramed, Inc., and i-Optics. No other author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…These differences might be explained by the instruments used for measurement; the thickness measured by FD-OCT was usually smaller than that measured by Pentacam or ultrasound pachymetry [ 14 , 19 ]. Our results were comparable to the mean CCT reported in normal adults measured using FD-OCT (532 μm in 66 eyes of subjects at a mean age of 35.39±10.6 years, and 537 μm in 561 eyes of subjects at a mean age of 45.70±21.20 years) [ 13 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…These differences might be explained by the instruments used for measurement; the thickness measured by FD-OCT was usually smaller than that measured by Pentacam or ultrasound pachymetry [ 14 , 19 ]. Our results were comparable to the mean CCT reported in normal adults measured using FD-OCT (532 μm in 66 eyes of subjects at a mean age of 35.39±10.6 years, and 537 μm in 561 eyes of subjects at a mean age of 45.70±21.20 years) [ 13 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…It could be the irregular corneal shape and thickness (although normalization of the epithelium following corneal cross-linking treatment minimizes the influence of this theory), as has been introduced by our team 7. It could be related to eye rubbing, although regular stability of the epithelial maps through long-term investigation also minimized the potential influence of this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, overall corneal epithelial thickness,4,5 as well as epithelial thickness topographic variability, may serve as diagnostic elements, in synergy with other topographic and Scheimpflug tomographic screening indicators, such as irregular corneal thickness6,7 and anterior-surface topographic variability 8,9…”
Section: Introductionmentioning
confidence: 99%
“…38 Cataract surgery can damage corneal epithelium and epithelial thickness is associated with local irregularities of corneal topography that contribute to the optical power of the cornea. 39 Furthermore, signi cant changes in epithelial thickness have been correlated with corneal instability. 40 It was found that epithelial thickness increased 1 day postoperatively and decreased after 1 week.…”
Section: Discussionmentioning
confidence: 99%